Effects of canagliflozin on serum potassium in people with diabetes and chronic kidney disease: the CREDENCE trial. (23rd August 2021) - Neuen, Brendon L; Oshima, Megumi; Perkovic, Vlado; Agarwal, Rajiv; Arnott, Clare; Bakris, George; Cannon, Christopher P; Charytan, David M; Edwards, Robert; Górriz, Jose L; Jardine, Meg J; Levin, Adeera; et al.
Abstract: Aims : Hyperkalaemia is a common complication of type 2 diabetes mellitus (T2DM) and limits the optimal use of agents that block the renin–angiotensin–aldosterone system, particularly in patients with chronic kidney disease (CKD). In patients with CKD, sodium‒glucose cotransporter 2 (SGLT2) inhibitors provide cardiorenal protection, but whether they affect the risk of hyperkalaemia remains uncertain. Methods and results : The CREDENCE trial randomized 4401 participants with T2DM and CKD to the SGLT2 inhibitor canagliflozin or matching placebo. In this post hoc analysis using an intention-to-treat approach, we assessed the effect of canagliflozin on a composite outcome of time to either investigator-reported hyperkalaemia or the initiation of potassium binders. We also analysed effects on central laboratory-determined hyper- and hypokalaemia (serum potassium ≥6.0 and <3.5 mmol/L, respectively) and change in serum potassium. At baseline, the mean serum potassium in canagliflozin and placebo arms was 4.5 mmol/L; 4395 (99.9%) participants were receiving renin–angiotensin system blockade. The incidence of investigator-reported hyperkalaemia or initiation of potassium binders was lower with canagliflozin than with placebo [occurring in 32.7 vs. 41.9 participants per 1000 patient-years; hazard ratio (HR) 0.78, 95% confidence interval (CI) 0.64–0.95, P  = 0.014]. Canagliflozin similarly reduced the incidence of laboratory-determined hyperkalaemia (HR 0.77, 95% CI 0.61–0.98, P  = 0.031), with no effect on the risk of hypokalaemia (HR 0.92, 95% CI 0.71–1.20, P  = 0.53). The mean serum potassium over time with canagliflozin was similar to that of placebo. Conclusion : Among patients treated with renin–angiotensin–aldosterone system inhibitors, SGLT2 inhibition with canagliflozin may reduce the risk of hyperkalaemia in people with T2DM and CKD without increasing the risk of hypokalaemia. Graphical Abstract: